Analisis Perbedaan Kinerja Keuangan Saat dan Pasca Pandemi Covid-19 sebagai Dampak dari Penerapan Strategi Cost Leadership - Luh Indira Kinasih Iswandar; Made Oka Candra Andreana (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
The Covid-19 pandemic has impacted several sectors, including the aviation industry, prompting company management to implement adaptive strategies such as cost efficiency to maintain operational continuity and financial health. This study uses a quantitative approach to examine differences in financial performance during and after the Covid-19 pandemic as a result of the implementation of a cost leadership strategy. Using secondary data from the annual report of I Gusti Ngurah Rai Airport, Bali, for the 2020–2024 period, the analysis used the Wilcoxon Signed Rank Test. The results show no significant difference in cost leadership between the pandemic and post-pandemic periods (Sig. 0.686), indicating consistent implementation. However, financial performance, as measured by Net Profit Margin, showed a significant difference (Sig. 0.043), increasing from a minimum value of –155% during the pandemic to a maximum of 30% post-pandemic. These findings suggest that there is a significant difference in financial performance due to the implementation of a cost leadership strategy, which plays a role in supporting recovery and improving financial performance after the crisis.